Manajemen Laba Sebelum dan Setelah Penerapan PSAK 71 pada Perusahaan Subsektor Perbankan di Indonesia - Amrie Firmansyah; Muhammad Rizky; Nurlaely Qodarina (Owner : Riset dan Jurnal Akuntansi, 2022)
The adoption of IFRS 9 through PSAK 71 impacts the greater discretionary space for managers to practice earnings management. This study investigates the difference in earnings management practices before and after the implementation of PSAK 71 in the banking sub-sector in Indonesia. This study uses quantitative methods, with data derived from the www.idx.co.id, www.ojk.go.id, and the company's official website for the 2019 and 2020 reporting periods. Based on purposive sampling, the total sample is 56 observations. This study's multiple linear regression test was employed to determine earnings management level. The earnings management results in 2019 and 2020 are then tested for differences to determine changes in managers' behavior in carrying out earnings management. This study finds no significant difference in earnings management practice that comes before and after the implementation of PSAK 71. The factors that caused no difference are the early adoption of PSAK 71 and the relaxation provisions due to the Covid-19 pandemic. This research is expected to be useful for investors as a basis for decision-making, as well as standard-setting bodies and the OJK in regulating and monitoring company earnings management practices.